A Framework for an Inferential Conception of Physical Laws - Cristian Soto; Otávio Bueno (Principia: An International Journal of Epistemology)
We advance a framework for an inferential conception of physical laws, addressing the problem of the application of mathematical structures to the relevant structure of physical domains. Physical laws, we argue, express generalizations that work as rules for deriving physically informative inferences about their target systems, hence guiding us in our interaction with various domains. Our analysis of the application of mathematics to the articulation of physical laws follows a threefold scheme. First, we examine the immersion of the relevant structure of physical domains into mathematical structures. Second, we assess the inferential power of laws resulting from the mathematical formalism employed in the immersion step. And third, we provide a suitable physical interpretation for the extant mathematical structures obtained from the inferential step. We demonstrate that a deflationary, empiricist framework for an inferential conception of physical laws delivers both an understanding of the mathematical character of physical laws, and a way of responding to some of the standard philosophical riddles associated with laws.